Fast and Accurate Simulation Method for Switch-Mode Power Supplies - Schmidt, Martin; Doebroenti, M.; Bucher, Alexander; Dürbaum, Thomas (PCIM Conference, May 2010, 2010)
In order to describe the voltage and current waveforms of a switch-mode power supply (SMPS) accurately by simulation the parasitic output capacitance of the MOSFET cannot be neglected. For this reason the paper describes and compares two different simulation methods which take this capacitance into account without extending the simulation time considerably, so that a fast and accurate transient simulation of the SMPS is obtained. The first method is an analytical solution with an equivalent linear capacitance. The second method really considers the non-linear dependency of the capacitance on the voltage. The measurement at the end shows, that the second method describes the SMPS very accurately. Furthermore a comparison with a calculation which neglects the parasitic capacitance shows the relevance of the proposed method. © 2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.fastan
Keywords: MOSFET; Simulation; SMPS